2011
DOI: 10.1590/s1516-89132011000600011
|View full text |Cite
|
Sign up to set email alerts
|

The cytogenetic effects of black tea and green tea on cultured human lymphocytes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
(44 reference statements)
0
7
0
Order By: Relevance
“…The mean MI and NDI among exposed group compared to control group were shown in Table 1. MI and NDI are markers for estimating the general toxicity. The proportion of metaphase cells and binucleated cells may be used as a biomarker of the lymphocytes mitogen response, immune functions and cytostatic effects of various studied agents included the low radiation dose exposure (Eroğlu, 2011, Alaloc & Eroğlu,2011. Table 1 showed that the MI of the exposed staff in diagnostic and interventional is slightly higher compared to control but statistically it is not significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…The mean MI and NDI among exposed group compared to control group were shown in Table 1. MI and NDI are markers for estimating the general toxicity. The proportion of metaphase cells and binucleated cells may be used as a biomarker of the lymphocytes mitogen response, immune functions and cytostatic effects of various studied agents included the low radiation dose exposure (Eroğlu, 2011, Alaloc & Eroğlu,2011. Table 1 showed that the MI of the exposed staff in diagnostic and interventional is slightly higher compared to control but statistically it is not significantly different.…”
Section: Resultsmentioning
confidence: 99%
“…26 Each group was treated daily for 7 and 14 consecutive days. 27 24 hours after the last treatment. Both femurs were dissected and bone marrow was flushed from the femoral cavity with fetal calf serum.…”
Section: Mn Assaymentioning
confidence: 99%
“…The slides were stained with giemsa and scored. MN was scored in 1000 binucleated cells and the frequency of cells with MN was determined (Eroğlu, 2011).…”
Section: Micronuclei Assaymentioning
confidence: 99%